Negative Pressure Wound Therapy in Surgical Wound Management: Mechanisms, Clinical Outcomes, and Comparative Analysis of Modern NPWT Systems - Marcjasz, Piotr; Bioły, Anna; Buliszak, Agnieszka; Babczyńska, Monika; Borończyk, Agnieszka; Zając, Piotr (Quality in Sport, 2025)
Introduction: Surgical wounds that fail to heal or that develop complications such as infection or dehiscence are challenging problem that health care has to deal with everyday. Negative Pressure Wound Therapy (NPWT) has emerged as an important tool for managing complex wounds. This review aims to summarize the mechanisms by which NPWT supports wound healing, estimate the clinical efficacy of NPWT in surgical wounds and compare available NPWT systems. Materials and methods: A literature review was conducted using the databases such as Pubmed and Google Scholar. State of Knowledge: NPWT involves a sealed dressing attached to a suction pump that applies subatmospheric pressure to the wound. There are four major mechanisms that lead straight to the effect: microdeformation [14]; macrodeformation [13], fluid removal [15]; stabilization of wound environment [11]. Clinically, NPWT has demonstrated improved healing rates in chronic wounds (e.g., diabetic foot ulcers) [5, 6] and decreased surgical site infection and seroma in high-risk surgical incisions [7, 8]. Conclusions: NPWT upgrades healing by stabilizing environment of wound, enhancing granulation and closing wound faster. Evidence confirms its efficacy in reducing wound complications in both open and closed surgical wounds. NPWT has become an invaluable tool in surgical wound management, however it is still important to use it in selected group of patients.